Glandular myxoma of left atrium: An uncommon tumor - Elugoti Divya; N Rukhmangadha; Rashmi Patnayak; Abha Chandra; Hari Krishna P Murthy (Heart India, 2016)
In the present day, there is an overall increase in the incidence of various tumors of the body though tumors of the heart are not common. Metastatic tumors of the heart are more common than primary tumors. Among primary tumors of the heart, myxoma is the most common tumor. However, glandular differentiation in myxoma is rare. Hereby, we present a rare case report of glandular differentiation in cardiac myxoma of the left atrium.